2021
DOI: 10.1155/2021/5520517
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Ketamine Infusion for Perioperative Pain Management in Patients Undergoing Laparoscopic Gastric Bypass: A Prospective Randomized Controlled Trial

Abstract: Introduction. Obesity is a common comorbidity seen in the perioperative setting and is associated with many diseases including cardiovascular disease and obstructive sleep apnea. Laparoscopic Roux-en-Y gastric bypass is the gold standard surgical treatment for patients whose weight is refractory to diet and exercise. Caring for these patients perioperatively presents unique challenges to anesthesiologists and is associated with an increased risk of adverse respiratory events. In our study, we hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Conversely, Ali et al observed that ketamine failed to decrease fentanyl consumption intraoperatively in obese patients undergoing abdominoplasty surgery. A study conducted by Seman et al showed ketamine reduced fentanyl consumption intraoperatively [ 21 ]. This discrepancy may be due to differences in infusion regimens across studies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Ali et al observed that ketamine failed to decrease fentanyl consumption intraoperatively in obese patients undergoing abdominoplasty surgery. A study conducted by Seman et al showed ketamine reduced fentanyl consumption intraoperatively [ 21 ]. This discrepancy may be due to differences in infusion regimens across studies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen (or paracetamol) significantly reduced the pain score at the end of anesthesia (MD: −1.88) [27,33], 2 h (MD: −1.53) [33], 8 h (MD: −1.8) [33], and 12 h (MD: −1.63) [33] after surgery (Table 1). Ketamine significantly reduced the pain score at 60 min (MD: −1.31) [20,40,49,50], 2 h (MD: −1.03) [20,40,49,50], and 12 h after surgery (MD: −0.43) [42,45,49,50] (Table 1). Dexmedetomidine significantly reduced the pain score at 30 min (MD: −1.36) [17,31,49], 60 min (MD: −1.24) [15,17,31,47,49], 2 h (MD: −0.87) [15,31,49], 4 h (MD: −3.10) [36], 6 h (MD: −0.44) [22,31,47,49], and 48 h (MD: −0.80) [17,47] after surgery (Table 1).…”
Section: Postoperative Painmentioning
confidence: 97%
“…The characteristics of the included RCTs are available for consultation in SMC2. An analysis shows that out of the total participants, 1795 patients were allocated to the control (1491 placebo or no intervention and 304 to a comparator), while 1775 were allocated to treatment (135 to Ibuprofen [28,33], 207 to acetaminophen (or paracetamol) [25,27,29,33], 329 to ketamine [16,20,37,39,40,42,43,45,49,50,52], 23 to ketamine plus clonidine [18], 68 to ketamine plus magnesium [39,42], 391 to dexmedetomidine [15,17,22,26,31,36,47,49], 341 to lidocaine [21,26,38,41,44,46,47,51], 70 to magnesium [34,48], 112 to gabapentin [23,32,35], 69 to pregabalin [19,30], and 30 to pregabalin plus dexmedetomidine [24]). Regarding the comparison between treatment and the comparator, acetaminophen was compared with ibuprofen in 89 patients …”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its incorporation into opioid-free anaesthesia (OFA) protocols has shown signi cant bene ts. Seman et al (2021) [5] reported that total perioperative opioid consumption was signi cantly lower in the ketamine group compared to the control group (179.9 morphine equivalents (ME) versus 248.7 ME, P = 0.03). Postoperative patient-controlled analgesia (PCA) opioid administration was also signi cantly lower in the ketamine group (90.6 ME versus 137.6 ME, p = 0.04).…”
Section: Introductionmentioning
confidence: 99%